Cobalt-based amorphous magnetically soft alloy material, preparation thereof and composite wave absorbing structure based on magnetically soft alloy

By adjusting the composition of the cobalt-based amorphous soft magnetic alloy material, a material with excellent soft magnetic properties was prepared and the surface was selected as the frequency, which solved the problem that existing composite wave absorbing materials were difficult to be light, wide frequency and simple in process, and achieved efficient wave absorbing performance and widely applicable wave absorbing structure.

CN119650237AActive Publication Date: 2025-03-18NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411806966.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing composite wave absorbing materials are difficult to have the comprehensive performance of lightweight, broadband and simple technology, and the comprehensive performance of amorphous soft magnetic alloy materials is poor.

Method used

Using a cobalt-based amorphous soft magnetic alloy material, a material with low saturation magnetic induction strength, low coercivity and high initial magnetic permeability was prepared by adjusting the atomic percentage content of Co, Fe, Ni, Si, B and Cr, and a composite wave absorbing structure was prepared, and the surface was selected based on the material as the frequency.

Benefits of technology

The lightweight and thin characteristics of the composite absorbing structure and significantly broadened absorption bandwidth are achieved, and both have good corrosion resistance and process simplicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650237A_ABST
    Figure CN119650237A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt-based amorphous magnetically soft alloy material, preparation thereof and a composite wave absorbing structure based on magnetically soft alloy. The alloy material comprises the following components: CoaFebNicSidBeCrf, 60 < = a < = 70, 2 < = b < = 6, 0.5 < = c < = 5, 10 < = d < = 20, 10 < = e < = 20, 0.5 < = f < = 5, and a + b + c + d + e + f = 100, and the alloy material has low saturation flux density, low coercive force and high initial permeability, and also has excellent corrosion resistance and oxidation resistance. The composite wave-absorbing structure obtained by taking the amorphous magnetically soft alloy material as the frequency selective surface is simple, the pattern of the frequency selective surface is simple, and the manufacturing cost is low; the prepared wave-absorbing material is low in total thickness, effective absorption bandwidth is greatly improved, and the wave-absorbing material has the characteristics of lightness, thinness and broadband absorption and is of great significance in promoting development of light, thin and broadband wave-absorbing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of amorphous soft magnetic alloy materials and composite wave absorbing structures, and in particular to a cobalt-based amorphous soft magnetic alloy material and a preparation method thereof, and a composite wave absorbing structure based on the soft magnetic alloy. Background Art

[0002] With the advancement of communication and artificial intelligence technology, the problem of electromagnetic radiation generated by electronic devices has become increasingly serious, which has made the research of absorbing materials crucial. Absorbing materials can absorb electromagnetic waves and are widely used in military and civilian fields. In the military, it is used for radar stealth and electromagnetic pulse protection to improve the battlefield survivability of weapons and equipment and protect personnel and equipment from radiation. In civilian use, absorbing materials are used to protect against electromagnetic radiation pollution and shield wireless communication equipment. With the continuous advancement of wireless communication technology, the potential hazards of electromagnetic radiation have increased, so the research and development of absorbing materials has received more and more attention.

[0003] However, traditional absorbing materials usually require a thicker absorption layer to achieve efficient absorbing effects, resulting in a large material thickness and weight. In addition, traditional absorbing materials usually have a broad absorption of electromagnetic waves within a certain frequency range, making it difficult to achieve selective absorption of specific frequencies and are usually difficult to use in practical applications.

[0004] Therefore, frequency selective surface (FSS) absorbing materials have the advantages of being lighter, thinner, more frequency selective, better thermally stable and multifunctional compared to traditional absorbing materials. These advantages make FSS absorbing materials have broad application prospects in the fields of communications, radar, stealth technology, etc. Among them, amorphous soft magnetic materials have unique physical and chemical properties, such as high magnetic permeability, high strength, light weight, corrosion resistance, flexibility and plasticity, etc. These properties make amorphous soft magnetic materials play an important role in the field of absorbing waves, and can realize the transition from traditional absorbing materials to new FSS absorbing materials, bringing new possibilities for electromagnetic wave absorption and stealth technology.

[0005] The Chinese patent document with publication number CN113782975A discloses a composite material with a deformed cross pattern and a square ring fractal topological pattern. The thickness of the absorbing material reaches 10 mm and the absorption bandwidth is about 10 GHz. The Chinese patent document with publication number CN117578091A discloses a frequency selective surface composite absorbing device with a miniaturized unit. The total absorbing material thickness is more than 7.05 mm and the absorption bandwidth may reach 16 GHz.

[0006] The Chinese patent document with publication number CN117748157A discloses a low-frequency bandwidth-expanded reconfigurable frequency selective surface composite absorbing device, the pattern of which is a dipole array, the total absorbing material thickness is between 5.025-40.8mm, and the absorption bandwidth covers 6.0GHz. The Chinese patent document with publication number CN209843961U discloses a frequency selective surface with a double-ring metal patch pattern, the total absorbing material thickness is 6.75mm, and the absorption bandwidth is 14.2GHz.

[0007] The above patents improve the absorbing performance of composite absorbing materials to varying degrees through frequency selective surface design, but these materials cannot simultaneously have comprehensive properties such as lightness, wide bandwidth and simple process, and it is difficult to prepare frequency selective surface composite absorbing materials with wide applicability. Therefore, the development of a frequency selective surface composite absorbing material that is both light, wide bandwidth and simple process is of great significance for promoting the development of frequency selective surface substrates and the promotion and application of cobalt-based amorphous soft magnetic alloy materials. Summary of the invention

[0008] In view of the problems that amorphous soft magnetic alloy materials have poor comprehensive performance and that existing composite absorbing materials are difficult to be both light and thin, broadband and simple in process, the present invention provides a cobalt-based amorphous soft magnetic alloy material, and uses the soft magnetic alloy material as a frequency selective surface to prepare a composite absorbing structure that has the advantages of being both light and thin and having a significantly widened absorption bandwidth.

[0009] To achieve the above object, the technical solution adopted by the present invention is:

[0010] A cobalt-based amorphous soft magnetic alloy material, wherein the cobalt-based amorphous soft magnetic alloy material composition has the following expression: Co a Fe b Ni c Si d B e Cr f , where a, b, c, d, e, and f represent the atomic percentage of the corresponding components, respectively, among which, 60≤a≤70, 2≤b≤6, 0.5≤c≤5, 10≤d≤20, 10≤e≤20, 0.5≤f≤5, a+b+c+d+e+f=100.

[0011] In the present invention, CoFeSiB material is used as the research basis, a small amount of Ni is used to improve the soft magnetic properties of the material, and a small amount of transition metal is added to improve the corrosion resistance and physical properties of the material, but the addition of transition metal will cause the partial magnetic permeability of the material to decrease and the amorphous forming ability to decrease. Different elements have different effects on different properties of the material, and they affect each other. The inventors found that the amorphous soft magnetic alloy composed of the above can have low saturation magnetic induction intensity, low coercive force and high initial magnetic permeability, and also has excellent corrosion resistance and oxidation resistance.

[0012] In some embodiments, the atomic percentage of Co in the cobalt-based amorphous soft magnetic alloy material is 60≤a≤68. For example, the value is 60.5, 61, 61.5, 62, 62.5, 63, 63.5, 64, 64.5, 65, 65.5, 66, 66.5, 67, 67.5, or any value therebetween; in some embodiments, preferably, 62≤a≤67.5; further preferably, 63≤a≤67; further preferably, 64≤a≤66.5; the cobalt-based amorphous alloy has lower saturation magnetic induction intensity and loss, and has higher magnetic permeability at high frequency, so it is easier to saturate, has a high rectangular ratio, and has good high-frequency magnetic properties.

[0013] In some embodiments, the atomic percentage of Fe in the cobalt-based amorphous soft magnetic alloy material is 3≤b≤5. For example, the value is 3.25, 3.5, 3.75, 4, 4.25, 4.5, 4.75, or any value therebetween; in some embodiments, preferably, 3.5≤b≤4.5; further preferably, 3≤b≤4; the appropriate iron content can reduce the coercive force of the amorphous alloy, increase the magnetic permeability and saturation magnetic induction intensity, thereby improving the soft magnetic properties.

[0014] In some embodiments, the atomic percentage of Ni in the cobalt-based amorphous soft magnetic alloy material is 1≤c≤3. For example, the value is 1.2, 1.25, 1.4, 1.5, 1.6, 1.75, 1.8, 2, 2.2, 2.4, 2.5, 2.6, 2.8, or any value therebetween; in some embodiments, preferably, 1.5≤c≤2.5; further preferably, 1≤c≤2; the addition of Ni can reduce the saturation magnetic induction intensity of the material to a certain extent, reduce the vacuum requirement of the sprayed strip and the oxidation phenomenon caused by the vacuum degree of the heat treatment process, but the addition of precious metals also increases the cost of raw materials.

[0015] In some embodiments, the atomic percentage of Si in the cobalt-based amorphous soft magnetic alloy material is 14≤d≤17. For example, the value is 14.25, 14.5, 14.75, 15, 15.25, 15.5, 15.75, 16, 16.25, 16.5, 16.75, or any value therebetween; preferably, in some embodiments, 14.5≤d≤16.5; further preferably, 15≤d≤16; the Si element can lower the melting point of the amorphous alloy, thereby making it easier to form an amorphous structure during rapid cooling or rapid solidification. In addition, the Si element can change the viscosity of the alloy, further promote amorphous formation, and improve the amorphous forming ability of the alloy.

[0016] In some embodiments, the atomic percentage of B in the cobalt-based amorphous soft magnetic alloy material is 10≤e≤15, such as 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, 14.5, or any value therebetween; preferably, in some embodiments, 10≤d≤14.

[0017] In some embodiments, the atomic percentage of Cr in the cobalt-based amorphous soft magnetic alloy material is 0.5≤f≤3.5, such as 0.75, 1, 1.25, 1.75, 2, 2.25, 2.5, 2.75, 3, 3.25, or any value therebetween;

[0018] In the present invention, a small amount of transition metal is used to improve the corrosion resistance of the material to adapt to more types of application environments. In some embodiments, the atomic percentage of Cr in the cobalt-based amorphous soft magnetic alloy material is 0.5≤f≤3, preferably 0.5≤f≤2. In this range, the soft magnetic properties of the material are good, and the overall amorphous forming ability of the material is strong. It is further preferred that 0.155≤f≤1.5.

[0019] In some embodiments, the total atomic percentage content of Co and Fe in the cobalt-based amorphous soft magnetic alloy material is 65≤a+b≤70.

[0020] Compared with other elements, the addition of Cr makes the alloy material have better amorphous forming ability, zero magnetostriction coefficient, maintains excellent soft magnetic properties at high temperature, and improves the corrosion resistance of the material.

[0021] In some embodiments, the purity of the Fe, Co, Ni, B, Si and Cr raw materials is above 99 wt. %. Preferably, the purity of all raw materials is above 99.5 wt. %.

[0022] The cobalt-based amorphous soft magnetic alloy material of the present invention has low saturation magnetic induction intensity, low coercive force, high initial magnetic permeability and high rectangular ratio, and has excellent soft magnetic properties.

[0023] The present invention also provides a method for preparing the cobalt-based amorphous soft magnetic alloy material, comprising the following steps: step 1, weighing each element raw material according to the alloy composition and smelting it into a master alloy ingot; step 2, making the master alloy ingot into an amorphous soft magnetic alloy strip.

[0024] In some embodiments, when the master alloy ingot is melted in step 1, the steps include: placing the weighed alloy raw materials in a melting device and melting them in an inert atmosphere; keeping the temperature for 5-20 minutes after melting, and then pouring the molten alloy ingot into a copper mold and cooling it for more than 30 minutes to obtain a master alloy ingot;

[0025] The above pure metal may be melted by any method, and for example, there is a method of melting the pure metal by high frequency heating after vacuuming the chamber. In addition, the master alloy and the finally obtained soft magnetic alloy usually have the same composition.

[0026] In some embodiments, the prepared raw materials are heated to be melted to obtain molten metal (molten metal). The temperature of the molten metal is not particularly limited, as long as all the raw materials can be melted, for example, 1300-1500°C.

[0027] Preferably, the smelting process is performed 1-3 times to ensure uniform distribution of the components in each alloy ingot.

[0028] In some embodiments, the preparation of the amorphous soft magnetic alloy strip in step 2 includes but is not limited to at least one of a single-roller rapid quenching method, a vacuum spray casting method, a medium frequency induction melting method, etc.;

[0029] Preferably, the amorphous soft magnetic alloy strip is prepared in step 2 by a single-roller rapid quenching method.

[0030] The "single-roll rapid quenching method" in the present invention refers to melting the ingot and pouring it onto the surface of a rotating water-cooled copper roller, rapidly cooling it to obtain an amorphous to microcrystalline thin strip. The preparation process is to use a high-speed rotating roller to rapidly cool the melt column into a thin strip.

[0031] In some embodiments, when the method for preparing the amorphous soft magnetic alloy strip in step 2 is a single-roller rapid quenching method, the process parameters of the single-roller rapid quenching method are: the injection pressure is 0.01-0.03MPa, and the copper rod rotation speed is 3000-5000r / min. In some embodiments, the process parameters of the single-roller rapid quenching method are preferably: the injection pressure is 0.01-0.03MPa, and the copper rod rotation speed is 3500-4500r / min.

[0032] Preferably, the process parameters of the single-roller rapid quenching method are: the injection pressure is 0.02 MPa, and the copper roll rotation speed is 4000 r / min.

[0033] In some embodiments, the single-roll rapid quenching method for preparing amorphous soft magnetic alloy strips specifically includes the following steps: crushing the mother alloy ingot and placing it in a quartz tube with a nozzle at the bottom; placing the quartz tube in a belt spinning machine to secondary melt the alloy ingot therein, and using the single-roll rapid quenching method to prepare a continuous alloy amorphous strip.

[0034] The present invention also provides the use of the cobalt-based amorphous soft magnetic alloy material as a material of a frequency selective surface layer in a composite wave absorbing device.

[0035] The present invention also provides a composite wave absorbing structure based on an amorphous soft magnetic alloy frequency selective surface, the composite wave absorbing structure comprises a first dielectric substrate layer, a frequency selective surface layer, and a second dielectric substrate layer from top to bottom; the material of the frequency selective surface layer is the cobalt-based amorphous soft magnetic alloy material. Each layer is bonded by dry glue.

[0036] There are relatively few reports in the prior art on using cobalt-based amorphous soft magnetic tape materials as frequency selective surface materials. The cobalt-based amorphous soft magnetic alloy of the present invention is used to prepare the frequency selective surface layer. It has low processing difficulty and good forming performance under the premise of ultra-thin thickness and simple pattern, and can achieve extremely high wave absorption performance. It has a wide effective absorption bandwidth and is suitable for occasions with limited space.

[0037] The frequency selective surface layer has a thickness of 0.02-0.05 mm and includes a plurality of FSS units arranged in a row and column period, with a row and column period of 10-90 mm; the FSS units are in an equal-length cross pattern, with a spacing of 45-60 mm.

[0038] The arm length of the cross pattern is 30-80 mm, and the arm width is 15-25 mm.

[0039] Preferably, the thickness of the first dielectric substrate layer is 1-2 mm, the real part of the complex dielectric constant ε' is 5.5-7.5, the imaginary part of the complex dielectric constant ε" is 0.1-1, the real part of the complex magnetic permeability μ' is 2.3-3.1, the imaginary part of the complex magnetic permeability μ" is 0.4-0.7, and the loss factor is 0.03-0.13.

[0040] Preferably, the thickness of the second dielectric substrate layer is 1-2 mm, the real part of the complex dielectric constant ε' is 15.5-17, the imaginary part of the complex dielectric constant ε" is 0.2-0.4, the real part of the complex magnetic permeability μ' is 3.1-4.3, the imaginary part of the complex magnetic permeability μ" is 0.6-1.9, and the loss factor is 0.02-0.03.

[0041] The material of the first dielectric substrate layer includes one or more of nickel-zinc ferrite, carbon fiber, and carbonyl iron, mixed with one or more of silicone, epoxy resin, and polyurethane;

[0042] The material of the second dielectric substrate layer includes one or more of nickel-zinc ferrite, carbon fiber, and carbonyl iron, mixed with one or more of silicone, epoxy resin, and polyurethane.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The cobalt-based amorphous soft magnetic alloy material under the specific composition of the present invention has excellent soft magnetic properties such as low saturation magnetic induction intensity, low coercive force and high initial magnetic permeability, and still maintains high amorphous forming ability without adding P element, and has excellent comprehensive performance.

[0045] (2) The cobalt-based amorphous soft magnetic alloy material of the present invention also has good corrosion resistance and long-term stability, is suitable for a variety of harsh environments, and has wide adaptability.

[0046] (3) The cobalt-based amorphous soft magnetic alloy material of the present invention does not contain rare earth metal elements and volatile elements, has low cost and stable performance; and does not contain harmful substances such as cadmium, lead, and mercury, and is friendly to human health and the environment.

[0047] (4) The cobalt-based amorphous soft magnetic alloy material in the present invention is used to prepare the frequency selective surface. The obtained composite absorbing device has a simple structure, a simple frequency selective surface pattern, and a low production cost. The total thickness is low, and the effective absorption bandwidth is greatly improved. It has the characteristics of light weight and wide-band absorption, which is of great significance for promoting the development of light weight and wide-band absorbing materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 1 is the XRD diffraction pattern of the cobalt-based amorphous alloy material in Examples 1, 2, 3 and Comparative Example 1.

[0049] Figure 2 3 and Comparative Example 1 show the saturation magnetic induction intensity variation curves of the cobalt-based amorphous alloy materials prepared in Examples 1, 2, 3 and Comparative Example 1.

[0050] Figure 3 1 and 2 are electrochemical curves of the cobalt-based amorphous alloy materials prepared in Examples 1, 2, 3 and Comparative Example 1.

[0051] Figure 4 Schematic diagram of modeling of composite wave absorbing structures based on frequency selective surfaces prepared in Examples 4-13 and Comparative Examples 2-3.

[0052] Figure 5 Graph showing the variation of reflection loss with frequency for Examples 4-13 and Comparative Examples 2-3.

[0053] Figure 6 Schematic diagram of the structure of the composite absorbing device prepared for the application example.

[0054] Figure 7 The graph of the absorbing performance of the composite absorbing device measured for an application example. DETAILED DESCRIPTION

[0055] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0056] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.

[0057] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.

[0058] The present invention provides the following specific embodiments and all possible combinations thereof. For the purpose of brevity, this application only lists several representative components to represent all possible combinations of the technical solutions.

[0059] Unless otherwise defined, all technical and scientific terms used in the specification of this application have the same meaning as those commonly understood by those skilled in the art of the technical field of this application. The terms used in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0060] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present application, the technical solution undoubtedly includes technical solutions connected by "logical and", and also undoubtedly includes technical solutions connected by "logical or".

[0061] For example, "A and / or B" includes three parallel solutions of A, B and A+B. For another example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution that is connected by "logical OR"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four items of A, B, C, and D (that is, the technical solution that is connected by "logical AND").

[0062] As used herein, the terms "comprising", "including" and "comprising" are synonymous and are inclusive or open-ended and do not exclude additional, unrecited members, elements or method steps.

[0063] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0064] In the present invention, "preferred", "better", "more preferred" and "suitable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0065] In the present invention, “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.

[0066] The raw materials used in the following specific embodiments are all purchased from the market.

[0067] Example 1

[0068] In this embodiment, the molecular formula of the cobalt-based amorphous soft magnetic alloy material is Co 65.07 Fe 3.94 Ni 0.99 Si 15B 14 Cr 1 , the specific preparation method of the alloy material is as follows:

[0069] Step 1: Raw materials Co, Fe, Ni, Si, B, and Cr with a purity greater than 99.5% are prepared according to the composition formula Co 65.07 Fe 3.94 Ni 0.99 Si 15 B 14 Cr 1 Carry out batching, and the weighing error is controlled within 0.0005g;

[0070] Step 2: Place the prepared raw materials into a clean alumina crucible, place it into an induction melting furnace, and evacuate it to below -0.002 Pa under an argon atmosphere. Keep the temperature for more than 10 minutes after melting, then pour the molten alloy into a copper mold and cool it in the furnace for 25 minutes to obtain a master alloy ingot with uniform composition;

[0071] Step 3: crush the master alloy ingot obtained in step 2 and put it into a quartz tube with a nozzle of about 60mm, adjust the distance between the tube mouth and the roller surface to about 0.25mm, and then evacuate to less than 0.02Pa. Adjust the pressure difference between the inside and outside of the quartz tube to 0.02MPa, adopt a single-roller rapid quenching belt-spinning process, and spin the belt at a speed of 40m / s under an argon protective atmosphere. That is, set the copper rod speed to 4000r / min and turn on the heating current. When the solenoid heats the molten master alloy ingot until it is completely melted and the white light jitter phenomenon is observed, turn off the heating current and press the injection button at the same time to obtain a continuous amorphous alloy strip. The strip width is 60mm and the thickness is 30μm.

[0072] Example 2

[0073] In this embodiment, the molecular formula of the cobalt-based amorphous soft magnetic alloy material is Co 64.14 Fe 3.89 Ni 0.97 Si 15 B 14 Cr 2 , the specific preparation method of the alloy material is as follows:

[0074] Step 1: Raw materials Co, Fe, Ni, Si, B, and Cr with a purity greater than 99.5% are prepared according to the composition formula Co 64.14 Fe 3.89 Ni 0.97 Si 15 B 14 Cr 2 Carry out batching, and the weighing error is controlled within 0.0005g;

[0075] Step 2: Place the prepared raw materials into a clean alumina crucible, place it into an induction melting furnace, and evacuate it to below -0.002 Pa under an argon atmosphere. Keep the temperature for more than 10 minutes after melting, then pour the molten alloy into a copper mold and cool it in the furnace for 25 minutes to obtain a master alloy ingot with uniform composition;

[0076] Step 3: crush the master alloy ingot obtained in step 2 and put it into a quartz tube with a nozzle of about 60mm, adjust the distance between the tube mouth and the roller surface to about 0.25mm, and then evacuate to less than 0.02Pa. Adjust the pressure difference between the inside and outside of the quartz tube to 0.02MPa, adopt a single-roller rapid quenching belt-spinning process, and spin the belt at a speed of 40m / s under an argon protective atmosphere. That is, set the copper rod speed to 4000r / min and turn on the heating current. When the solenoid heats the molten master alloy ingot until it is completely melted and the white light jitter phenomenon is observed, turn off the heating current and press the injection button at the same time to obtain a continuous amorphous alloy strip. The strip width is 60mm and the thickness is 30μm.

[0077] Example 3

[0078] In this embodiment, the molecular formula of the cobalt-based amorphous soft magnetic alloy material is Co 63.21 Fe 3.83 Ni 0.96 Si 15 B 14 Cr 3 , the specific preparation method of the alloy material is as follows:

[0079] Step 1: Raw materials Co, Fe, Ni, Si, B, and Cr with a purity greater than 99.5% are prepared according to the composition formula Co 63.21 Fe 3.83 Ni 0.96 Si 15 B 14 Cr 3 Carry out batching, and the weighing error is controlled within 0.0005g;

[0080] Step 2: Place the prepared raw materials into a clean alumina crucible, place it into an induction melting furnace, and evacuate it to below -0.002 Pa under an argon atmosphere. Keep the temperature for more than 10 minutes after melting, then pour the molten alloy into a copper mold and cool it in the furnace for 25 minutes to obtain a master alloy ingot with uniform composition;

[0081] Step 3: crush the master alloy ingot obtained in step 2 and put it into a quartz tube with a nozzle of about 60mm, adjust the distance between the tube mouth and the roller surface to about 0.25mm, and then evacuate to less than 0.02Pa. Adjust the pressure difference between the inside and outside of the quartz tube to 0.02MPa, adopt a single-roller rapid quenching belt-spinning process, and spin the belt at a speed of 40m / s under an argon protective atmosphere. That is, set the copper rod speed to 4000r / min and turn on the heating current. When the solenoid heats the molten master alloy ingot until it is completely melted and the white light jitter phenomenon is observed, turn off the heating current and press the injection button at the same time to obtain a continuous amorphous alloy strip. The strip width is 60mm and the thickness is 30μm.

[0082] Comparative Example 1

[0083] In this embodiment, the molecular formula of the cobalt-based amorphous soft magnetic alloy material is Co 66 Fe 4 NiSi 15 B 14 , the specific preparation method of the alloy material is as follows:

[0084] Step 1: Raw materials Co, Fe, Ni, Si, B with a purity greater than 99.5% are prepared according to the composition formula Co 66 Fe 4 NiSi 15 B 14 Carry out batching, and the weighing error is controlled within 0.0005g;

[0085] Step 2: Place the prepared raw materials into a clean alumina crucible, place it into an induction melting furnace, and evacuate it to below -0.002 Pa under an argon atmosphere. Keep the temperature for more than 10 minutes after melting, then pour the molten alloy into a copper mold and cool it in the furnace for 25 minutes to obtain a master alloy ingot with uniform composition;

[0086] Step 3: crush the master alloy ingot obtained in step 2 and put it into a quartz tube with a nozzle of about 60mm, adjust the distance between the tube mouth and the roller surface to about 0.25mm, and then evacuate to less than 0.02Pa. Adjust the pressure difference between the inside and outside of the quartz tube to 0.02MPa, adopt a single-roller rapid quenching belt-spinning process, and spin the belt at a speed of 40m / s under an argon protective atmosphere. That is, set the copper rod speed to 4000r / min and turn on the heating current. When the solenoid heats the molten master alloy ingot until it is completely melted and the white light jitter phenomenon is observed, turn off the heating current and press the injection button at the same time to obtain a continuous amorphous alloy strip. The strip width is 60mm and the thickness is 30μm.

[0087] Performance Testing

[0088] Figure 1The figure shows the XRD patterns obtained by using an X-ray diffractometer of model D8 ADVANCE to characterize the structure of the alloy strips prepared in Examples 1, 2, 3 and Comparative Example 1. It can be seen from the patterns that all alloy materials have only one broadened diffuse diffraction peak at 45 degrees, which is a typical amorphous diffuse scattering peak, indicating that the obtained alloy material is a completely amorphous structure with excellent amorphous forming ability.

[0089] Figure 2 The image shown is obtained by using a vibrating sample magnetometer (VSM, Vibrating Sample Magnetometer, LakeShore: 7410 model) to test the saturation magnetic induction intensity of the alloy materials prepared in Examples 1, 2, 3 and Comparative Example 1. It can be seen from the figure that the saturation magnetic induction intensity of the alloy materials in the examples is significantly lower than that in the comparative example, and is lower than 0.55T, while maintaining a relatively high squareness ratio. This shows that the alloy components in the present invention can effectively improve the soft magnetic properties of the alloy material, and the low saturation magnetic induction intensity enables the material to have better low-frequency magnetic properties, thereby increasing the effective absorption bandwidth of the absorbing material.

[0090] The soft magnetic properties test results of the amorphous alloy materials prepared in the embodiments and comparative examples are summarized as shown in Table 1. It can be seen that by regulating the proportion of Co, Fe, and Ni elements and adding different contents of Cr elements, the magnetic properties of the alloy can be significantly affected. When the Co content is reduced from 65.07 to 63.21, the Fe content is reduced from 3.94 to 3.83, and the Ni content is reduced from 0.99 to 0.96, as the Cr content is gradually increased, the saturation magnetization of the alloy shows an obvious upward trend, from 43.37emu / g to 54.58emu / g. Although the saturation magnetic induction intensity is slightly reduced (from 0.52T to 0.39T), compared with the comparative sample without adding Cr element, the present invention is expected to obtain more excellent comprehensive performance by the introduction of Cr element while maintaining good magnetic properties by accurately controlling the proportion of each element.

[0091] Table 1: Soft magnetic properties of amorphous alloy materials prepared in Examples and Comparative Examples

[0092]

[0093] Figure 3Shown is the potential polarization curve obtained by using Chenhua CHI660E electrochemical workstation to test the corrosion resistance of the alloy materials obtained in Examples 1, 2, 3 and Comparative Example 1. In order to better simulate the actual situation and obtain accurate test results, a three-electrode system was used in this test experiment. Among them, a saturated calomel electrode was used as a reference electrode, a platinum electrode was used as an auxiliary electrode, and a 3.5wt.% NaCl solution (pH=7) was selected as the electrolyte solution. The similarity with actual applications was specially considered in the design of the experiment, and the alloy strip was directly immersed in the electrolyte solution as a working electrode. Before the test officially started, the surface of the alloy sample needed to be polished to remove the oxide film on the surface. In addition, in order to ensure the smooth progress of the experiment, we also took additional precautions, namely wrapping the sharp corners of the sample with paraffin to prevent unnecessary discharge in these areas. These detailed considerations help to improve the reliability and practical value of the experimental data.

[0094] Figure 3 The polarization curve test results show that compared with the comparative example, the corrosion potential (Ecorr) of the embodiment moves positively, the corrosion current density decreases, and an obvious passivation interval appears. This shows that the addition of Cr element improves the corrosion resistance of the alloy, and the formed passivation film further inhibits corrosion. This improvement not only enhances the stability of the alloy during preparation and use, but also reduces the requirements for the vacuum environment, thereby helping to reduce production costs.

[0095] The cobalt-based amorphous soft magnetic alloy material prepared in Example 1 was used as the frequency selective surface, and CST STUDIOSUITE 2019 was used to simulate and prepare the composite absorbing structure to obtain the performance of the composite absorbing structure.

[0096] Example 4

[0097] Step 1: Start CST STUDIO SUITE 2019 software; select the "Microwave&RF" module on the main interface to enter the electromagnetic simulation setting interface;

[0098] Step 2:

[0099] 2-1. Modeling of the upper dielectric plate: In the modeling window, select "Create"-"Brick" to create a rectangular frame; set the size parameters of the rectangular frame: length = 90mm, width = 90mm, height = 2mm; define the material properties, select "New Material" in the "Material" menu, and enter the electromagnetic parameters of the material, and name it "Absorber1"; apply the material properties to the created rectangular frame;

[0100] 2-2. Modeling of the lower dielectric plate: In the modeling window, repeat the steps of creating a rectangular frame and set its size parameters: length = 90mm, width = 90mm, height = 1.5mm; set its position parameters to keep a certain distance from the upper dielectric plate; define the material properties, select "New Material" in the "Material" menu, and enter the electromagnetic parameters of the material and name it "Absorber2"; apply the material properties to the created rectangular frame;

[0101] 2-3. Frequency Selective Surface (FSS) Modeling: In the modeling window, select "Create" - "Polygon" - "Cross" to draw a cross pattern; set the size parameters of the pattern (arm length = 35mm, arm width = 25mm, thickness = 0.03mm), and define it in the middle of the dielectric plate; define the material properties, select "New Material" in the "Material" menu, enter the electromagnetic parameters of the material (S = 7.14E7, M = 1.5), and name it "FSS Material"; apply the material properties to the created cross pattern and arrange it as follows Figure 4 As shown, the rows and columns are arranged in a periodic extension, and the spacing of the cross pattern is 55 mm; the position parameters of the pattern relative to the upper dielectric plate and the lower dielectric plate are set so that it is located in the middle.

[0102] Step 3:

[0103] 3-1. Boundary conditions: In the "Boundary Conditions" menu, Z min Select "electric(Et=0)" to simulate a perfect conductor; Z max Select "Open (add space)" to simulate open space; set the min and max boundaries of X and Y to "unit cell";

[0104] 3-2. Excitation source: In the "Simulation" menu, select "Waveguide Port" to define the excitation source; set the frequency range of the excitation source (1GHz to 18GHz); locate the position of the excitation port so that it coincides with the incident surface of the model;

[0105] 3-3. Meshing: The meshing is set to automatic tetrahedral meshing.

[0106] Step 4: In the "Solver" menu, select "Transient Solver" or "Frequency DomainSolver"; set the simulation frequency step to 0.017GHz; click the "Start" button to start the simulation calculation;

[0107] Step 5: Select "S-Parameters" to view the curve graph of the scattering parameter S11 changing with frequency; export the simulation results, and organize and analyze them.

[0108] Comparative Example 2

[0109] Step 1: Start CST STUDIO SUITE 2019 software; select the "Microwave&RF" module on the main interface to enter the electromagnetic simulation setting interface;

[0110] Step 2:

[0111] 1. Modeling of the upper dielectric plate: In the modeling window, select "Create"-"Brick" to create a rectangular frame; set the size parameters of the rectangular frame: length = 90mm, width = 90mm, height = 2mm; define the material properties, select "New Material" in the "Material" menu, and enter the electromagnetic parameters of the material, and name it "Absorber2"; apply the material properties to the created rectangular frame;

[0112] 2. Modeling of the lower dielectric plate: In the modeling window, repeat the steps of creating a rectangular frame and set its size parameters: length = 90mm, width = 90mm, height = 1.5mm; set its position parameters to keep a certain distance (0.03mm) from the upper dielectric plate; define the material properties, select "New Material" in the "Material" menu, and enter the electromagnetic parameters of the material and name it "Absorber1"; apply the material properties to the created rectangular frame;

[0113] Step 3:

[0114] 1. Boundary conditions: In the "Boundary Conditions" menu, select "electric (Et = 0)" for Zmin to simulate a perfect conductor; select "Open (add space)" for Zmax to simulate open space; set the min and max boundary settings of X and Y to "unit cell".

[0115] 2. Excitation source: In the "Simulation" menu, select "Waveguide Port" to define the excitation source; set the frequency range of the excitation source (1GHz to 18GHz); locate the position of the excitation port so that it coincides with the incident surface of the model;

[0116] 3. Meshing: Meshing is set to automatic tetrahedral meshing;

[0117] Step 4: In the "Solver" menu, select "Transient Solver" or "Frequency DomainSolver"; set the simulation frequency step to 0.017GHz; click the "Start" button to start the simulation calculation;

[0118] Step 5: Select "S-Parameters" to view the curve graph of the scattering parameter S11 changing with frequency; export the simulation results, and organize and analyze them.

[0119] Examples 5-13 and Comparative Example 3

[0120] According to the steps of Example 4, the material parameters used in modeling the upper and lower dielectric plates, as well as the arm length and arm width of the cross-shaped pattern in the frequency selective surface are adjusted. The specific changed parameters and the absorbing performance of the composite absorbing structure obtained by simulation are shown in Table 2. The electromagnetic parameters corresponding to the dielectric plate materials simulated in the embodiment and the comparative example are shown in Table 3.

[0121] Table 2 Wave absorbing performance of composite wave absorbing structure obtained by simulation of embodiment and comparative example

[0122]

[0123] Table 3 Electromagnetic parameters corresponding to dielectric plate materials of the embodiment and comparative example simulation

[0124]

[0125] The data in Table 2 studies the influence of different structural parameters on the wave absorption effect. Through a systematic study of parameters such as material, thickness, arm length, arm width, and spacing, it is found that a wider effective absorption bandwidth can be obtained when the upper layer uses Absorber1 material, which is increased to 14.7GHz compared to 4.0GHz when using Absorber4 material, because Absorber1 has a lower dielectric constant and moderate magnetic permeability. In contrast, although Absorber4 has a similar dielectric constant, its loss factor is significantly higher. This combination of material properties enables Absorber1 to achieve better impedance matching, thereby obtaining a wider effective absorption bandwidth;

[0126] In terms of structural dimensions, the combination of an upper layer with a thickness of 2mm and a lower layer with a thickness of 1.5-2mm exhibits excellent wave absorption performance. When the thickness of the lower layer increases from 1.5mm to 2mm, the maximum absorption can be increased from -22.6dB to -26.7dB. This is because when the thickness of the lower layer increases, the higher dielectric and electromagnetic properties of Absorber2 provide stronger electromagnetic wave attenuation capabilities.

[0127] In terms of geometric parameters, the study found that a smaller arm width (5mm) can significantly increase the maximum absorption to -41.4dB, because a narrower arm width is conducive to better impedance matching at a specific frequency point, but it also limits the realization of broadband characteristics. Therefore, in practical applications, it is necessary to select the appropriate arm width parameter between bandwidth and absorption intensity according to specific needs. The arm length is most suitable at around 35mm. Too long will lead to a decrease in absorption performance. For example, when the arm length increases to 65mm, the maximum absorption drops to -16.3dB, because the excessive arm length will cause impedance mismatch and reduce the absorption effect; at the same time, the spacing parameters also have an important influence on the absorbing performance. A larger spacing has a better absorption effect than a smaller spacing, because a suitable spacing is conducive to the formation of effective electromagnetic coupling between adjacent units.

[0128] Through the optimized combination of the above parameters, broadband and strong absorption wave absorption characteristics can be achieved, providing a reliable design basis for practical applications.

[0129] The reflection loss of Examples 4-13 and Comparative Examples 2-3 varies with frequency as shown in Figure 5 As shown, it can be seen that in improving the absorbing performance of the amorphous soft magnetic frequency selective surface composite absorbing material, we optimize the propagation path of the electromagnetic wave in the material by adjusting the thickness of the upper and lower dielectric plates, thereby enhancing the absorbing effect; in addition, by precisely controlling the dielectric constant and magnetic permeability of the upper and lower dielectric plates, the propagation speed and attenuation characteristics of the electromagnetic wave can be changed, effectively improving the absorption performance within a specific frequency range; by adjusting the arm length and arm width of the cross-cross frequency selective surface, selective absorption of specific frequencies and expansion of the absorption band can be achieved, respectively, thereby significantly improving the overall absorbing performance within a multi-band range.

[0130] Application Examples

[0131] The cobalt-based amorphous soft magnetic alloy of the present invention can be used to manufacture high-performance radar absorbing materials, and is particularly suitable for military equipment such as stealth fighters. The specific application process is as follows:

[0132] The amorphous soft magnetic material strip of Example 1 was cut into a cross pattern, and the geometric parameters are shown in Table 4; the cut alloy strips were arranged on the dielectric plate in a cross pattern, the first dielectric plate was carbonyl iron + silica gel, with a thickness of 2 mm, and the second dielectric plate was carbonyl iron + silica gel, with a thickness of 1.5 mm. The actual measurement of the dielectric plate represents the actual measurement results of the first dielectric plate + the second dielectric plate without adding a frequency selective surface. Figure 6 As a schematic diagram of the pattern arrangement in this application example, a frequency selective surface composite absorbing device with a multilayer structure is constructed, and the reflectivity of the obtained composite absorbing device is tested using VNA, Agilent N5234A vector network analyzer.

[0133] Figure 7It is shown that, according to tests, the composite material using the material of the present invention increases the effective absorption bandwidth (RL≤-10dB) of the original dielectric plate from 2.6GHz to 9.4GHz in the range of 1-18GHz.

[0134] Table 4 Parameters and performance data of each surface in the application example

[0135]

[0136] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A cobalt-based amorphous soft magnetic alloy material, characterized in that: The cobalt-based amorphous soft magnetic alloy material composition has the following expression: Co a Fe b Ni c Si d B e Cr f , where a, b, c, d, e, and f represent the atomic percentage of the corresponding components, respectively, among which, 60≤a≤70, 2≤b≤6, 0.5≤c≤5, 10≤d≤20, 10≤e≤20, 0.5≤f≤5, a+b+c+d+e+f=100.

2. The cobalt-based amorphous soft magnetic alloy material according to claim 1, characterized in that: The atomic percentage of Co in the cobalt-based amorphous soft magnetic alloy material is 65≤a≤70; The atomic percentage of Fe in the cobalt-based amorphous soft magnetic alloy material is 3≤b≤5; The atomic percentage of Ni in the cobalt-based amorphous soft magnetic alloy material is 0.5≤c≤2; The atomic percentage of Si in the cobalt-based amorphous soft magnetic alloy material is 14≤d≤17; The atomic percentage of B in the cobalt-based amorphous soft magnetic alloy material is 10≤e≤15; The atomic percentage content of Cr in the cobalt-based amorphous soft magnetic alloy material is 0.5≤f≤3.

5.

3. The cobalt-based amorphous soft magnetic alloy material according to claim 1, characterized in that: The atomic percentage content of Cr in the cobalt-based amorphous soft magnetic alloy material is 0.5≤f≤3.

4. The method for preparing a cobalt-based amorphous soft magnetic alloy material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: step 1, weighing raw materials of various elements according to the alloy composition and then smelting them into a master alloy ingot; step 2, making the master alloy ingot into an amorphous soft magnetic alloy strip.

5. The method for preparing a cobalt-based amorphous soft magnetic alloy material according to claim 4, characterized in that: The preparation of the amorphous soft magnetic alloy strip in step 2 includes at least one of a single-roller rapid quenching method, a vacuum spray casting method, and a medium-frequency induction melting method.

6. The method for preparing a cobalt-based amorphous soft magnetic alloy material according to claim 4, characterized in that: When the method for preparing the amorphous soft magnetic alloy strip in step 2 is a single-roller rapid quenching method, the process parameters of the single-roller rapid quenching method are: the injection pressure is 0.01-0.03MPa, and the copper rod rotation speed is 3000-5000r / min.

7. Use of the cobalt-based amorphous soft magnetic alloy material according to any one of claims 1 to 3 as a material for a frequency selective surface layer in a composite wave absorbing device.

8. A composite wave absorbing structure based on an amorphous soft magnetic alloy frequency selective surface, characterized in that: The composite absorbing structure comprises, from top to bottom, a first dielectric substrate layer, a frequency selective surface layer, and a second dielectric substrate layer; the material of the frequency selective surface layer is the cobalt-based amorphous soft magnetic alloy material according to any one of claims 1-3.

9. The composite wave absorbing structure based on amorphous soft magnetic alloy frequency selective surface according to claim 8, characterized in that: The frequency selective surface layer has a thickness of 0.02-0.05 mm and includes a plurality of FSS units arranged in a row and column period, wherein the row and column period is 10-90 mm; the FSS units are in a cross pattern of equal length, and the spacing of the cross pattern is 5-60 mm.

10. The composite wave absorbing structure based on the amorphous soft magnetic alloy frequency selective surface according to claim 9, characterized in that: The arm length of the cross pattern is 30-85 mm, and the arm width is 15-25 mm.

11. The composite wave absorbing structure based on amorphous soft magnetic alloy frequency selective surface according to claim 8, characterized in that: The thickness of the first dielectric substrate layer is 1-2 mm, the real part of the complex dielectric constant ε' is 5.5-7.5, the imaginary part of the complex dielectric constant ε" is 0.1-1, the real part of the complex magnetic permeability μ' is 2.3-3.1, the imaginary part of the complex magnetic permeability μ" is 0.4-0.7, and the loss factor is 0.03-0.

13.

12. The composite wave absorbing structure based on amorphous soft magnetic alloy frequency selective surface according to claim 8, characterized in that: The thickness of the second dielectric substrate layer is 1-2 mm, the real part of the complex dielectric constant ε' is 15.5-17, the imaginary part of the complex dielectric constant ε" is 0.2-0.4, the real part of the complex magnetic permeability μ' is 3.1-4.3, the imaginary part of the complex magnetic permeability μ" is 0.6-1.9, and the loss factor is 0.02-0.

03.

13. The composite wave absorbing structure based on amorphous soft magnetic alloy frequency selective surface according to claim 8, characterized in that: The material of the first dielectric substrate layer includes one or more of nickel-zinc ferrite, carbon fiber, and carbonyl iron, mixed with one or more of silicone, epoxy resin, and polyurethane; The material of the second dielectric substrate layer includes one or more of nickel-zinc ferrite, carbon fiber, and carbonyl iron, mixed with one or more of silicone, epoxy resin, and polyurethane.

Citation Information

Patent Citations

  • Cobalt-base block amorphous soft magnetic alloy with high amorphous forming ability and preparation method thereof

    CN102915820A

  • Low-coercivity low-loss cobalt-based amorphous soft magnetic alloy material and preparing method thereof

    CN106498310A

  • Cobalt-based amorphous soft magnetic alloy material and preparation method and application thereof

    CN117867417A

  • Alloy particles

    US20230212722A1

  • Very thin soft magnetic alloy strips and magnetic core and electromagnetic apparatus made therefrom

    US5096513A